A prospective, randomised, open label study to compare efficacy and safety of hydroxychloroquine and teneligliptin in patients of type 2 diabetes mellitus refractory to concomitant metformin and glimepiride - Anand, Manisha; Randhawa, Gurpreet Kaur; Salwan, Surinder Kumar (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Diabetes mellitus is chronic, metabolic disease characterized by hyperglycemia, which over time causes both microvascular and macrovascular complications. If HbA1c target is not achieved with dual therapy then 3rd drug is added. Aims of present study were to compare efficacy and safety of Hydroxychloroquine (HCQ) and Teneligliptin in patients of T2DM who are refractory to concomitant Metformin and Glimepiride. Methods: It was interventional, randomized, prospective, parallel and open-label study. Patients were randomly divided into 2 groups either HCQ 400mg OD or Teneligliptin 20mg OD were added to their current treatment using Metformin 1gm BD and Glimepiride 4 mg OD as 3rd drug. Follow up was done every 15 days for 12 weeks and underwent assessment of glycaemic parameters (FBS, PPG, HbA1c), LFT, RFT, CBC, ADRs and VAS in addition to anthropometric parameters. Results: After 12 weeks of treatment, HCQ group showed statistically (p<0.05) better improvement in BMI than Teneligliptin group. Both groups showed comparable improvement (p>0.05) from baseline in FBS, HbA1c, PPG and VAS score. In HCQ group there was significant number (p<0.05) of patients who achieved target glycaemic control (HbA1c ≤7.5%) i.e., 56.6%, compared to 37% with Teneligliptin group. Both groups had comparable (p>0.05) safety profile with no serious adverse effects and no significant change (p>0.05) in hepatic, renal and complete blood profiles. Conclusions: On the basis of effects of HCQ on the glycaemic parameters and BMI, HCQ may be preferred over Teneligliptin in patients of T2DM who are refractory to concomitant Metformin and Glimepiride.